The Influence of Flexible Working Hours and Compensation on Employee Well-Being among University Lecturers in Indonesia with Work-Life Balance as Mediating Variable - Muhammad Dio Febrian; Zainnur M. Rusdi; Dina Safitri (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
Flexible working hours arrangements have been implemented in Indonesia, particularly for university lecturers who are responsible for teaching, research, and community service. The Lecturer Workload System (BKD) and Semester Credit Units (SKS) serve as the basis for workload regulation, now supported by flexible work policies to enhance lecturers’ well-being. This study aims to analyze the influence of flexible working hours and compensation on employee well-being among lecturers, with work-life balance as a mediating variable. A quantitative approach was employed, with lecturers from various universities as respondents. Convergent validity was tested using loading factor and average variance extracted, while reliability was assessed through composite reliability and Cronbach’s alpha. The results show that flexible working hours significantly affect both work-life balance and lecturers’ well-being, directly and through mediation. However, compensation has no significant effect on work-life balance and does not indirectly influence well-being through the mediating variable. Nevertheless, compensation still has a direct significant effect on employee well-being. These findings highlight the importance of implementing flexible work policies and maintaining a fair compensation system to support the well-being and productivity of university lecturers.